The Effect of AI (Artificial Intelligence) in Education on Student Motivation: A Systematic Literature Review - Badarudin; Lalu Parhanuddin; Ahmad Tohri; Muhammad Suhardi (Universitas Pendidikan Ganesha, 2025)
The lack of student learning motivation has become a critical issue in higher education, particularly in the digital era marked by rapid technological advancement. This study aims to analyze the contribution of artificial intelligence (AI) implementation in enhancing students’ learning motivation through a Systematic Literature Review (SLR) approach. The review was conducted by systematically screening scholarly literature in the Google Scholar database through several selection stages. The initial search using the keyword